AI-Driven Natural Language Processing in Healthcare: Transforming Patient-Provider Communication - Sarella, Prakash Nathaniel Kumar; Mangam, Vinny Therissa (Indian Journal of Pharmacy Practice)
Healthcare communication is the lifeblood of effective patient care. The ability of patients and providers to exchange information, comprehends diagnoses, and collaboratively make decisions directly influences healthcare outcomes. In this context, AI-powered NLP has emerged as an invaluable agent of change, revolutionizing the way medical information is conveyed, understood, and acted upon. Through a comprehensive exploration, this review article unpacks the multifaceted facets of AI's role in healthcare communication. It begins by elucidating the essence of AI-powered NLP, providing readers with a foundational understanding of these transformative technologies. Subsequently, it delves into the myriad benefits that AI brings to the table, ranging from improved patient engagement and accessibility to streamlined clinical documentation and augmented diagnosis and treatment support. However, it's not all progress without pause. This review also delves into the ethical considerations intrinsic to AI in healthcare communication, such as safeguarding patient privacy and addressing bias and equity concerns. As the review work unfolds, it scrutinizes the challenges that must be surmounted to effectively implement AI-driven communication solutions in healthcare settings while casting a visionary gaze into the future, discerning the uncharted horizons where AI might further elevate healthcare communication.
Keywords: AI; Natural Language Processing; Healthcare; Patient-Provider Communication; Quality of Care; Patient Experience